Eating culture :an anthropological guide to food - Crowther, Gillian (University of Toronto press, 2018)
From ingredients and recipes to meals and menus across time and space, this highly engaging overview illustrates the important roles that anthropology and anthropologists play in understanding food and its key place in the study of culture.